Helicobacter pylori vacA c1 Genotype Is a Benefit Biomarker for Prediction of Gastric Cancer Risk in Ardabil - Bakhti, Seyedeh Zahra; Gholizadeh, Shokofeh; Latifi-Navid, Saeid; Zahri, Saber; Yazdanbod, Abbas (International Clinical Neuroscience Journal, 2016)
BACKGROUND: Gastric cancer (GC) is the fifth common malignant disease and the third leading cause of cancer-related mortality in the world. Ardabil, a Northwestern province of Iran, includes the highest rate of GC within the country. Helicobacter pylori (H. pylori) vacA gene plays a major role in generating and maintaining the gastric inflammatory response, which alters the enteric nervous system in various combinations and may contribute to the development of GC. The aim of the current study was to investigate the relationship of the vacA c-region genotypes of H. pylori with GC among Ardabil population. METHODS: A total of 197 from 259 patients with non-atrophic gastritis (NAG) and GC, who were H. pylori positive, were selected and genotyped. RESULTS: The frequency of vacA c1 was 53.7% and c2 42.3%. There was a significant difference between the frequencies of vacA c1 in isolates from GC than those from NAG (p<0.05). Though the GC was considered as a dependent factor by the multiple logistic regression analysis, the vacA c1 genotype was significantly associated with age- and sex-adjusted risk for GC (p=0.003, odds ratio [OR] = 5.48; 95% confidence interval [CI] =1.80–16.63). CONCLUSION: It was proposed that the H. pylori vacA c1 genotype could be considered as an important determinant for prediction of risk of GC in Ardabil. It is suggested that interaction between H. pylori vacA c-region genotypes and gastric nervous system may contribute to the development of GC.